The Sunken Billions : The Economic Justification for Fisheries Reform - World Bank; Food and Agriculture Organization (World Bank, 2012)
This study and previous studies indicate that the current marine catch could be achieved with approximately half of the current global fishing effort. In other words, there is massive overcapacity in the global fleet. The excess fleets competing for the limited fish resources result in stagnant productivity and economic inefficiency. In response to the decline in physical productivity, the global fleet has attempted to maintain profitability by reducing labor costs, lobbying for subsidies, and increasing investment in technology. Partly as a result of the poor economic performance, real income levels of fishers remain depressed as the costs per unit of harvest have increased. Although the recent changes in food and fuel prices have altered the fishery economy, over the past decade real landed fish prices have stagnated, exacerbating the problem. The value of the marine capture seafood production at the point of harvest is some 20 percent of the $400 billion global food fish market. The market strength of processors and retailers and the growth of aquaculture, which now accounts for some 50 percent of food fish production, have contributed to downward pressure on producer prices. In technical terms, this study estimates the loss of potential economic rent in the global fishery. For the purposes of this study, economic rent is considered broadly equivalent to net economic benefits, which is the term used throughout most of the report. This study estimated the difference between the potential and actual net economic benefits from global marine fisheries using 2004 as the base year. The estimate was made using a model that aggregated the world's highly diverse fisheries into a single fishery. This made it possible to use the available global fisheries data such as production, value of production, and global fisheries profits as inputs to the model.